Cosmological signs in Quran: Twelve planets and the ultimate fate of the universe - Irmak, Mehmet Kemal (Journal of Islam and Science, 2023)
The Quran contains many scientific signs about Astronomy and Cosmology. For example, the verse 12:4 indicates that there exist twelve planets around the Sun. The new order of the planets may therefore be as Mercury, Venus, Earth, Mars, Jupiter, Saturn, Uranus, Neptune, Pluto, Haumea, Makemake and Eris. A number of verses indicate that with respect to the Earth, there exist seven cosmic layers in the universe; first of which is the solar system. The remaining 6 layers seem to be as follows: Milky Way Galaxy, The Local Group, Local Supercluster, Virgo Supercluster, Laniakea Supercluster and Highest layer: remaining parts of the universe. The verse 51:47 indicates that we live in an expanding universe and all the matter, energy and space in the universe was once squeezed into a small volume. Other verses indicate that ultimate fate of the universe seems to be Big Rip (rupture) in which the matter of the universe, from galaxies and stars to atoms and subatomic particles would be progressively torn apart by the accelerated expansion of the universe. This separation, a "ripping" of stars, planets and atoms would leave the universe entirely devoid of structure but the Ether. With the conception that the Ether (superfluid or plasma in nature) is the primary form of all substance, it could also form the basis of the permanent element in the Eternal World.